Measuring consistent poverty in Ireland with EU SILC data - Christopher T. Whelan; Brian Nolan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2006)
In this paper we seek to make use of the newly available Irish component of the European Union Statistics on Income and Living Conditions (EU-SILC) in order to develop a measure of consistent poverty that overcomes some of the difficulties associated with the original indicators employed as targets in the Irish National Anti-Poverty Strategy. Our analysis leads us to propose a set of economic strain indicators that cover a broader range than the original basic deprivation set. The accumulated evidence supports the view that a revised consistent poverty measure that combines a threshold of two or more economic strain items with income poverty at seventy per cent of median income, identifies those exposed to generalised deprivation arising from lack of resources in a manner consistent with their use as targets in the National Anti-Poverty Strategy. The consistently poor differ from others not only in relation to income poverty and economic strain but also in terms of exposure to a range of life-style deprivations and subjective economic pressures.
Keywords: 330; consistent poverty; economic strain; deprivation; multidimensional; direct measurement; reliability